Modern Methods of Preparing the children on Preschool Educational Organizations - Jabbarov, A.; Qarshiyeva, Z. (Indonesian Journal of Education Methods Development, 2020)
This paper makes analyses of the modern methods of preparing the children on Preschool educational organizations. On these cases, different research points of the innovative research were mentioned on preschool educational organizations. It concludes with the different research analyses to make better investigations in further